The complication rate following Neodymium-doped Yttrium Aluminum Garnet laser posterior capsulotomy for posterior capsular opacification in patients with and without comorbidities - Rajesh S Joshi; Pallavi Doble (Indian Journal of Ophthalmology, 2023)
Purpose: To study the complication rate following Nd: YAG posterior capsulotomy posterior capsular opacification (PCO) in patients with and without comorbid conditions. Methods: This was a prospective, interventional, comparative, and observational study. A total of 80 eyes, consisting of 40 eyes without ocular comorbidities (group A) and 40 eyes with ocular comorbidities (group B) that were being treated with Nd: YAG capsulotomy for PCO, were included. Visual outcome and complications of Nd: YAG capsulotomy were studied. Results: The mean age of group A patients was 61.65 ± 8.85 years and that of group B patients was 63 ± 10.46 years. Of the total, 38 (47.5%) were men and 42 (52.5%) were women. In group B, the ocular comorbidities were moderate nonproliferative diabetic retinopathy (NPDR) (n = 14 eyes; 14/40 = 35%), subluxated intraocular lens (IOL; <2 clock hours of subluxation; n = 6), age-related macular degeneration (ARMD; n = 6), post-uveitic eyes (having old signs of uveitis, no episode of uveitis since the last 1 year; n = 5), and operated cases of traumatic cataract (n = 4). The mean energy required in groups A and B was 46.95 ± 25.92 and 42.62 ± 21.85 mJ, respectively (P = 0.422). The average energy requirement in Grade 2, Grade 3, and Grade 4 PCO was 22.30, 41.62, and 79.52 mJ, respectively. An increase in intraocular pressure (IOP) of >5 mmHg from pre-YAG levels was observed in one patient in each group on day 1 postprocedure, for which medical treatment was given to both patients for 7 days. One patient in each group had IOL pitting. No patient had any other complications attributable to ND:YAG capsulotomy. Conclusion: Nd:YAG laser posterior capsulotomy is a safe procedure for PCO in patients with comorbidities. Visual outcomes were excellent after Nd:YAG posterior capsulotomy. Although a transient increase in IOP was noted, the response to treatment was good and a long-term increase in IOP was not observed.